A scalable voltage controlled oscillator for multi-rate high-speed interfaces. (September 2016) - Demartinos, Andreas C.; Tsimpos, Andreas; Vlassis, Spyridon; Souliotis, George; Sgourenas, Savvas
Abstract: This paper proposes a voltage controlled oscillator (VCO) which is based on a pseudo-differential ring oscillator suitable for multi-Gbps serial interfaces. The delay element employed in the ring oscillator topology consists of two CMOS inverters loaded by a simple negative resistance realized with pMOS transistors. The proposed topology is designed and simulated in a 65 nm CMOS process with 1.2 V supply voltage. As a realistic application, the VCO performance is optimized to be compliant with the MIPI Alliance M-PHY standard which is the most updated high-speed serial interface technology. The frequency tuning range covers the three frequency bands of the MPHY standard which are [0.624 and 0.7288] GHz, [1.248 and 1.4576] GHz and [2.496 and 2.9152] GHz and corresponds to high-speed gear 1, 2 and 3, respectively. In each gear an almost constant K VCO is achieved while the current consumption of the whole system is 2.87, 5.19 and 10.06 mA for the gears 1, 2 and 3, respectively. The phase noise is about −94 dBc/Hz at 1 MHz frequency offset for 2.9152 GHz.